Simultaneous ultra‐performance liquid chromatography–tandem mass spectrometry determination of six components in rat plasma after oral administration of Smilacis glabrae Roxb. extract. (8th September 2019) - Xie, Jing; Li, Li; Shi, Yurui; Chen, Rongda; Liu, Guiming; Wang, Mengxue; Zheng, Meizhu; Zhang, Ning
Abstract: In this study, an accurate and reliable method of ultra‐performance liquid chromatography coupled with a triple‐quadrupole tandem mass spectrometry was firstly developed and fully validated for the simultaneous determination of epicatechin, neoastilbin, astilbin, isoastilbin, engeletin and resveratrol in rat plasma after administration of Smilacis glabrae Roxb. extract. Naringenin was used as an internal standard (IS). The analyte and IS were separated on a C18 column by gradient elution with a mobile phase of acetonitrile–0.3% acetic acid at a flow rate of 0.25 mL/min for a total run time of 8 min. The method was validated in terms of selectivity, linearity, precision, accuracy, extraction recovery, matrix effect and stability. The developed method was successfully applied to determine the main pharmacokinetic parameters of six components in rat plasma.